Tahap Identifikasi Awal Keaslian Artefak Budaya pada Elemen Struktur Rumoh Aceh - Suhartina, Wijayanti; Atthaillah, Atthaillah; Mirsa, Rinaldi; Iqbal, Muhammad; Badriana, Badriana (Nature : National Academic Journal of Architecture, 2024)
The presence of traditional Acehnese houses, known as rumoh Aceh, is becoming increasingly scarce, particularly those that are still used as community residences. Currently, rumoh Aceh can be classified into three categories: those that are still inhabited, those that are abandoned, and replicas. Replicas of rumoh Aceh can be found as venues for cultural activities during certain times or used as museums. This research examines the use of rumoh Aceh as residences, as well as those that are no longer inhabited and replicas that are used as museums. The study aims to ensure the originality of rumoh Aceh by observing its structural elements. It is important to note that in the future, rumoh Aceh may only be found as replicas. The aim is to observe the quality of the replicated object compared to the non-replicated Aceh rumoh object. The survey method and visual documentation were used to observe these elements based on the literature. The study compared the structural elements of non-replica houses with those of replica houses. It was discovered that the replica of rumoh Aceh, specifically rumoh Cut Nyak Meutia, lacked some essential structural elements. This finding is significant, particularly in the context of preserving the values and completeness of cultural artifacts for replication efforts.